Interdisciplinary research on food environments: key to transforming unhealthy food consumption practices and unsustainable food systems - Müller-Hansen, Merle; Mahne-Bieder, Johannes; Keck, Markus (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
Since the Covid-19 pandemic, digital services such as apps for food and health have become much more widely used, especially in urban settings, where the majority of human society now resides. Therefore, the context in which food choices are made have changed significantly. We suggest that understanding food environments and their entanglements with dynamics of digitalization, corporeality, and power relations can contribute to an improved analysis of the interrelations between food systems, public health, and sustainability. In this short communication, we call the attention of food scholars to the under-researched dimensions in food environment debates and invite medical, psychology, and sustainability scientists to engage in a concerted effort to comprehend food environments as key to transform unhealthy food consumption practices and unsustainable food systems.